ANALYSIS OF EFFECT COMMUNICATION, LEADERSHIP AND TEAM WORK FOR EMPLOYEE DISCIPLINE OF X HOSPITAL SURABAYA - Dila, Afifah Nasyahta; Rochmah, Thinni Nurul (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTDiscipline is one of significant factors that increase the employeeâs perfomance. One of discipline indicators is absenteeism. Absenteeism rate of employee in 2014 was high especially for alpa (22,35%). Purpose of this research analyze communication, leadership and team work influence to discipline employees.This research using cross sectional method. Respondents are 36 employees. The sampling through stratified random sampling. The location is in a hospital. The result of this research showed the effectivity of communication level is in moderate cathegory (50%). The hospital leadership has supported employees to be discipline (50%). The effetivity of team work level is high (77,8%). The result of linier regression tests between dependent variable with several independent variables showed that communication (p=0,024) and teamwork (0,004) variables influence employees discipline.Based on the results, to enhance the effectivity of communication by regulating information flow and utilizing feedback. To enhance the effectivity of team work by making an event can increase the flexibility, cohesivity, viability dan communication team such as outbound.Keywords: communication, discipline,Â  leadership and teamwork